Chaff in the Winds of War? The Arandora Star, Not Forgetting and Commemoration at the 80th Anniversary. (1st October 2020) - Colpi, Terri
ABSTRACT: This article discusses the sinking of the SS Arandora Star on 2 July 1940 and the legacy of this wartime event in relation to the 'historic' Italian community in Britain. Selection of Italians for deportation and the significant loss of life are interrogated contextually and in terms of psychological consequences. The new concept 'pockets of affect' is introduced in considering unevenness of geographical impact and also energy in commemorative enterprise, for which post-generations are now responsible. Developments in British and Italian literature and narrative formation are examined, elucidating changing attitudes in both countries. In 2020, at the 80 th anniversary of the 'tragedy', continued prominence of the Arandora Star in collective memory ensures a widening of the mnemonic community.